The Effects of the Use of Serious Game in Eco-Driving Training - Hrimech, Hamid; Beloufa, Sabrina; Merienne, Frederic; Boucheix, Jean Michel; Cauchard, Fabrice; Vedrenne, Joël; Kemey, Andras (Frontiers in ICT, 2016)
Serious games present a promising approach to training and learning. The player is engaged in a virtual environment for a purpose beyond pure entertainment, all while having fun. In this paper, we investigate the effects of the use of serious game in eco-driving training. An approach has been developed in order to improve players’ practical skills in term of eco driving. This approach is based on the development of driving simulation based on serious game, integrating a multisensorial guidance system with metaphors including visual messages (information on fuel consumption, ideal speed area, gearbox management…) and sounds (spatialized sounds, voice messages…). The results demonstrate that the serious game influence positively the behavior of inexperienced drivers in ecological driving, leading to a significant reduction (up to 10%) of their CO2 emission. This work brings also some guidelines for the design process. The experiences lead to a determination of the best eco-driving rules allowing a significant reduction of CO2 emission.